2019
DOI: 10.29271/jcpsp.2019.04.309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity Surgery on Restless Leg Syndrome

Abstract: Restless leg syndrome (RLS), which is a chronic neurosensory-motor disorder, is a disease which is usually accompanied by disturbing or unpleasant sensations, characterised by an irresistible impulse for moving the legs. This sensation which may be as a severe pain may temporarily relieve with movements.Prevalence of RLS varies between 4% and 10% in the general population. 1 RLS, which is characterised by delay in starting sleep, difficulty to maintain sleep, decreased total sleeping time and impairment in slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Supporting the correlation between obesity and RLS, a study by Ozdas et al has demonstrated that weight loss obtained with bariatric surgery lead to an improvement of RLS symptoms, with around 86% of patients that discontinued medications after 12 months from bariatric surgery [69].…”
Section: Obesity and Restless-leg Syndromementioning
confidence: 93%
“…Supporting the correlation between obesity and RLS, a study by Ozdas et al has demonstrated that weight loss obtained with bariatric surgery lead to an improvement of RLS symptoms, with around 86% of patients that discontinued medications after 12 months from bariatric surgery [69].…”
Section: Obesity and Restless-leg Syndromementioning
confidence: 93%